Desain Perancangan Sistem Pakar Diagnosa Penyakit Saluran Pernapasan Berbasis Web - Rayuwati Rayuwati; Amna Abdurrahman (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
Acute Respiratory Infection (ARI) is a very serious health problem in Indonesia. According to the Basic Health Research (RISKESDAS) the highest ARI diseases were in the provinces of East Nusa Tenggara (41.7%), Papua (31.1%), Aceh (30.0%), West Nusa Tenggara (28.3%), and East Java (28.3%). In Riskesdas 2007, East Nusa Tenggara is also the province with the highest ARI. The time period for the spread of ARI in Indonesia according to Riskesdas in 2013 was 25.0%, not much different from that in 2007 which was 25.5%. People are sometimes reluctant to go to the doctor and tend to ignore this disease. For solutions to these problems, we need a system that can help the community in diagnosing respiratory disorders so that later the community can more easily consult to anticipate a worse impact. One system that can be used to assist diagnosis is an expert system. This system is not to replace the position of an expert, but to promote the knowledge and experience of an expert.